2015
DOI: 10.1002/tea.21306
|View full text |Cite
|
Sign up to set email alerts
|

Investigating optimal learning moments in U.S. and finnish science classes

Abstract: This study explores how often students are engaged in their science classes and their affective states during these times, using an innovative methodology that records these experiences in situ. Sampling a subset of high schools in the U.S. and Finland, we collected over 7,000 momentary responses from 344 students over the course of a week. We examine engagement within and between students in different environments identifying common social and emotional factors they may be experiencing in their science classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
116
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(125 citation statements)
references
References 50 publications
(63 reference statements)
8
116
0
1
Order By: Relevance
“…However, feeling challenged is a normal and necessary part of learning. Students appear to experience optimal learning when their skill, interest, and challenge are balanced (Schneider et al, 2016). Recent interventions aim to help students' resilience and shift toward more malleable conceptions of intelligence (Good et al, 2003; Bages and Martinot, 2011; Yeager and Dweck, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, feeling challenged is a normal and necessary part of learning. Students appear to experience optimal learning when their skill, interest, and challenge are balanced (Schneider et al, 2016). Recent interventions aim to help students' resilience and shift toward more malleable conceptions of intelligence (Good et al, 2003; Bages and Martinot, 2011; Yeager and Dweck, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by previous research, such as the study by Goetz and colleagues (2015) who described clusters of situations in which at least moderate levels of boredom occurred together with positive affect. Likewise, stress has been associated with positive emotions and motivation in situations in which students feel challenged but also feel that they have the skills to keep up with current challenges (e.g., Schneider et al, 2016). That tiredness is associated with both positive and negative emotions may not be surprising given that it is not associated with a particular valence but rather labelled an "other affective states:…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, these findings have generated research on affect in online and computer‐supported learning environments (e.g., Baker, D'Mello, Rodrigo, & Graesser, ; Wosnitza & Volet, ) and in science learning settings (e.g., Schneider et al, ). The increase of computer‐supported inquiry and computer‐supported collaborative inquiry in learning environments that strive for authenticity, such as virtual laboratories in science, technology, engineering, and mathematics (STEM) classrooms, calls for an understanding of the impact of technologies on affect in learning.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding achievement outcomes, Niculescu et al's study () in mathematics and statistics revealed that achievement outcomes could be predicted by learning‐related emotions. For optimal learning in science (i.e., intense domain‐specific engagement), students are more likely to feel confident , successful , and happy and also perceive science as important to them if they are appropriately challenged (Schneider et al, ). Notably, Linnenbrink‐Garcia et al's study () revealed a connection between positive affect and positive group interactions in high school collaborative mathematics tasks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation